Synergistic effects of palm oil and cordierite partial-flow particulate filter on thermal efficiency and emission characteristics of a 2.5L diesel vehicle - Huy Quang Dang; Mek Srilomsak; Preechar Karin; S. Srimanosaowapak; Vitoon Uthaisangsuk; Chinda Charoenphonphanich (Case Studies in Thermal Engineering, 2026)
This study experimentally evaluates the synergistic effects of palm oil biodiesel fuels and a cordierite-based partial-flow diesel particulate filter (P-DPF) on the thermal efficiency and emission characteristics of a 2.5L light-duty diesel vehicle, using commercial fuels (B7 and B10) and neat biodiesel (B100). Steady-state chassis dynamometer tests showed that P-DPF installation increased exhaust backpressure by up to 7.2 kPa while causing only minor changes in fuel consumption and brake thermal efficiency. Under the New European Driving Cycle, B100 inherently reduced particulate number (PN) and mass (PM) by more than 43% and 32%, respectively, compared to commercial fuels. The integration of the P-DPF further reduced PN by 36–40% and PM by 57–60%. In addition, catalytic oxidation decreased CO and THC emissions by up to 20–25%, while NOx emissions were reduced by up to 20%, likely due to the combined effects of biodiesel properties and mild internal EGR induced by increased backpressure. Despite these improvements, the combined application remained insufficient to meet the Euro 5 limit but supported partial compliance with Euro 4 standards. These results demonstrate a practical and cost-effective retrofit strategy for reducing emissions from aging diesel vehicles. Particulate matter under the New European Driving Cycle, with and without the installation of P-DPF, (a) real-time concentration of the particulate number, (b) particulate number, and (c) particulate mass.
Keywords: Biodiesel Production and Applications; Advanced Combustion Engine Technologies; Catalytic Processes in Materials Science